Public-Private Partnerships and Digital Transformation: A New Approach to Local Development in Tunisia - Cyrine BAHRI (New Advances in Business, Management and Economics Vol. 6, 2025)
Nowadays, faced with various challenges, the territory is at the heart of every development strategy. Indeed, it represents the focus of public action, a domain where institutional and non-institutional policymakers, as well as development practitioners, contribute. Local development relies on its ability to improve living standards within territories and enhance their economic attractiveness to foreign investments. However, achieving this goal requires the implementation of a set of tools that integrate managerial, relational, and legislative dimensions. These tools are closely linked to innovation and the ability of local authorities to leverage technologies, particularly Information and Communication Technologies (ICT). Digitalisation plays a crucial role in transforming territories by strengthening their attractiveness at various levels, simplifying administrative procedures, and fostering social cohesion. In this context, digital technology has become central to the modernisation strategy of the Tunisian administration. Various initiatives have been launched to bring public services closer to citizens, enhance procedural transparency, and combat corruption. This chapter examines the relationship between digital innovation and local development, emphasising the impact of this dynamic on territorial transformation. To achieve this, theoretical proposals have been developed to better understand this relationship. The study adopts an interpretivist paradigm underpinned by an abductive reasoning approach. Given the multifaceted nature of digital transformation in local governance, the aim is to develop a nuanced understanding of how digitalisation is affecting local development in Tunisia. To address the complexity of the subject matter, an exploratory qualitative methodology has been employed, integrating both primary and secondary data sources to capture a comprehensive view of the ongoing transformation. The findings reveal several obstacles hindering the effectiveness of Public-Private Partnerships (PPPs) based on digital innovation. Nevertheless, efficient management of digital resources can have a significant impact on local and territorial development, particularly within the Tunisian context. In the public sector, the adoption of digital tools is a pivotal element for administrative success. For digital transformation to effectively bridge the gap between administration and citizens, it requires strong leadership commitment. The conclusion provides valuable insights into development models in a state undergoing transformation. While the adoption of digital technologies in Tunisia, especially through PPPs, has demonstrated substantial benefits in terms of economic and administrative efficiencies, there remains a critical need for ongoing research to refine the measures of innovation and better understand the interplay between resource mobilisation, innovation, and territorial development.